Determination of Ca, Mg, and Zn in biodiesel microemulsions by FAAS using discrete nebulization - Amais, Renata S.; Garcia, Edivaldo E.; Monteiro, Marcos R.; Nobrega, Joaquim A. [UNESP] (Elsevier B.V., 2012)
In this work an analytical procedure was developed for calcium, magnesium, and zinc determination in biodiesel samples using flame atomic absorption spectrometry based on microemulsion formation for sample preparation and discrete aspiration for sample introduction. The microemulsions were composed by biodiesel, Triton X-100, HNO3 20% (v v (1)), and n-propanol 10:5:5:80 (v v (1)). External calibration was carried out employing inorganic standards and light mineral oil was used for simulating the matrix of biodiesel samples. Relative standard deviations (RSD) were lower than 4.0%, 2.2% and 5.7% (n = 10) for Ca, Mg and Zn, respectively. Matrix effects were not observed when the standard additions method was applied. Sensitivities by using discrete aspiration for Ca, Mg and Zn were 2.5, 6.1, and 7.0-fold, respectively, better than those obtained when employing conventional continuous aspiration. Accuracy was checked by addition and recovery experiments for different types of biodiesel samples (African oil palm, castor beans, palm, and soybeans), and recoveries ranged from 90.8% to 115%. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; FAAS; Metals; Microemulsion